Assessing the magnitude and trends in hospital acquired infections in Canadian hospitals through sequential point prevalence surveys. Issue 1 (December 2016) - Taylor, Geoffrey; Gravel, Denise; Matlow, Anne; Embree, Joanne; LeSaux, Nicole; Johnston, Lynn; Suh, Kathryn; John, Michael; Embil, John; Henderson, Elizabeth; Roth, Virginia; Wong, Alice
Abstract Background Healthcare acquired infections (HAI) are an important public health problem in developed countries, but comprehensive data on trends over time are lacking. Prevalence surveys have been used as a surrogate for incidence studies and can be readily repeated. Methods The Canadian Nosocomial Infection Surveillance Program conducted prevalence surveys in 2002 and 2009 in a large network of major Canadian acute care hospitals. NHSN definitions of HAI were used. Use of isolation precautions on the survey day was documented. Results In 2009, 9, 953 acute care inpatients were surveyed; 1, 234 infections (124/1000) were found, compared to 111/1000 in 2002, (p < 0.0001). There was increased prevalence of urinary tract infection (UTI) andClostridium difficile, offset by decreases in pneumonia and bloodstream infection. Use of isolation precautions increased from 77 to 148 per 1000 patients (p < 0.0001), attributable to increased use of contact precautions in patients infected or colonized with antimicrobial resistant organisms. Conclusion Between 2002 and 2009 HAI prevalence increased by 11.7 % in a network of major Canadian hospitals due to increases inClostridium difficile and urinary tract infection. The use of isolation precautions increased by 92.2 % attributable to increased contact isolation. National prevalence surveys are useful tools to assess evolving trends in HAI.